2009
DOI: 10.2307/25474659
|View full text |Cite
|
Sign up to set email alerts
|

Test Anxiety, Academic Achievement, and Self-Esteem among Arab Adolescents with and without Learning Disabilities

Abstract: The aim of the current study was twofold: (a) to explore differences in test anxiety and self-esteem between adolescents with learning disabilities (LD) and those without them; (b) and to study the relationship between test anxiety and academic achievement. This research is the first to consider these relationships among Christian Arab adolescents living in Israel as an Eastern collectivist minority. Before the final examination of the first semester of the school year, 102 Christian Arab students completed Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
44
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 52 publications
12
44
0
5
Order By: Relevance
“…Nevertheless, we expect that age differences will vary in the sub-categories of test anxiety. We hypothesise that cognitive obstruction and tenseness will be higher among young adult college students than among adolescent high school students, following the trend that test anxiety increases with age revealed in previous studies (McDonald, 2001;Peleg, 2009). We suggest that social derogation may be higher among adolescents than among young adults.…”
Section: Test Anxiety and Agesupporting
confidence: 54%
See 1 more Smart Citation
“…Nevertheless, we expect that age differences will vary in the sub-categories of test anxiety. We hypothesise that cognitive obstruction and tenseness will be higher among young adult college students than among adolescent high school students, following the trend that test anxiety increases with age revealed in previous studies (McDonald, 2001;Peleg, 2009). We suggest that social derogation may be higher among adolescents than among young adults.…”
Section: Test Anxiety and Agesupporting
confidence: 54%
“…Previous research 660 O. Dan et al has suggested that in general, college-aged young adults suffer from higher test anxiety compared with school-aged adolescent students (Peleg, 2009). Nevertheless, we expect that age differences will vary in the sub-categories of test anxiety.…”
Section: Test Anxiety and Agementioning
confidence: 98%
“…The self in this culture is part of the group rather than an independent entity; thus the success or failure of an individual becomes that of the family as a whole. As a result, IA students may feel shame, guilt, and fear that they might lose their parents' support, and this may trigger anxiety [39]. Our results may be seen in a similar perspective.…”
Section: Questionnairesupporting
confidence: 53%
“…However, the groups had similar ATQ-N scores. We believe that the Eastern collectivistic features of the IA group [39] were overcame by anxiety-provoking tendencies of their being a minority, their difficulty to enter the Israeli life and Israeli colleges, and perhaps due to their pressure to achieve in a society that gives them too few chances due to their minority status [17][18][19][20]. Arab youngsters experience pressure from their parents on many life issues, and especially on personal choices as college studies.…”
Section: Questionnairementioning
confidence: 99%
See 1 more Smart Citation